Para além da barreira dos números: desigualdades raciais e saúde - Lopes, Fernanda (2005)
The point of departure for this article was the concept of health as a set of comprehensive and collective living conditions, influenced by the political, socioeconomic, cultural, and environmental context. The work thus shows that studies on health inequalities, disparities, or iniquities should extend beyond statistical data, since racism is not always explicit and measurable in social interactions. It is necessary to analyze the various life experiences of blacks and non-blacks in a given social condition, considering gender, age, place of residence, schooling, family origin, occupation, income, sexual orientation, religious affiliation, capacities and incapacities, social network, and possibilities for accessing social goods and services. Finally, the article lists guidelines that can assist in the major challenge of drafting public policies to combat and eradicate the immense inequalities between whites and blacks.